ArleKin: Learning together - Silva, Ana Maria Costa e; Moisan, André; Carvalho, Maria de Lurdes; Fortecöef, Clarisse (Advances in Social Sciences Research Journal, 2016)
This paper presents the experience related to developing a training course on Mediation for Social Inclusion through European Mobility within a project funded by the European Union between 2013 and 2016. The course is based on the training scheme of the Tour of France Companions in which trainees learn their role by observing and working with their masters in different cities. Social mediation, as the jobs were at that time, is learnt through immersion in various contexts. This course is still being developed in France and in other countries and it has been updated by the authors of the paper, through the use of Web 2.0. The course uses action-research-training methodology in which experiential, reflective and collaborative dimensions are present. In total, five countries and 13 Associations for Mediation participated along with the team responsible for in the project.